Association between urinary per- and poly-fluoroalkyl substances and COVID-19 susceptibility. (August 2021) - Ji, Junjun; Song, Lingyan; Wang, Jing; Yang, Zhiyun; Yan, Haotian; Li, Ting; Yu, Li; Jian, Lingyu; Jiang, Feixiang; Li, Junfeng; Zheng, Jinping; Li, Kefeng
Graphical abstract: Highlight: There is an urgent need for identifying risk factors for COVID-19 susceptibility. PFASs exposure was associated with an increased risk of COVID-19 infection. Metabolic disturbances in mitochondrial stress signaling and immune responses. PFASs-associated metabolites were correlated with clinical biomarkers. Abstract: Background and Objective: The growing impact of the COVID-19 pandemic has heightened the urgency of identifying individuals most at risk of infection. Per- and poly-fluoroalkyl substances (PFASs) are manufactured fluorinated chemicals widely used in many industrial and household products. The objective of this case-control study was to assess the association between PFASs exposure and COVID-19 susceptibility and to elucidate the metabolic dysregulation associated with PFASs exposure in COVID-19 patients. Methods: Total 160 subjects (80 COVID-19 patients and 80 symptom-free controls) were recruited from Shanxi and Shandong provinces, two regions heavily polluted by PFASs in China. Twelve common PFASs were quantified in both urine and serum. Urine metabolome profiling was performed by liquid chromatography coupled with tandem mass spectrometry (LC-MS/MS). Results: In unadjusted models, the risk of COVID-19 infection was positively associated with urinary levels of perfluorooctanesulfonic acid (PFOS) (Odds ratio: 2.29 [95% CI: 1.52–3.22]), perfluorooctanoic acid (PFOA) (2.91, [1.95–4.83], and total PFASs (∑ (12) PFASs) (3.31, [2.05–4.65]). After controlling for age, sex, body mass index (BMI), comorbidities, and urine albumin-to-creatinine ratio (UACR), the associations remained statistically significant (Adjusted odds ratio of 1.94 [95% CI: 1.39–2.96] for PFOS, 2.73 [1.71–4.55] for PFOA, and 2.82 [1.97–3.51] for ∑ (12) PFASs). Urine metabolome-PFASs association analysis revealed that 59% of PFASs-associated urinary endogenous metabolites in COVID-19 patients were identified to be produced or largely regulated by mitochondrial function. In addition, the increase of PFASs exposure was associated with the accumulation of key metabolites in kynurenine metabolism, which are involved in immune responses (Combined β coefficient of 0.60 [95% CI: 0.25–0.95, P  = 0.001]). Moreover, alternations in PFASs-associated metabolites in mitochondrial and kynurenine metabolism were also correlated with clinical lab biomarkers for mitochondrial function (serum growth/differentiation factor-15) and immune activity (lymphocyte percentage), respectively. Conclusion: Elevated exposure to PFASs was independently associated with an increased risk of COVID-19 infection. PFASs-associated metabolites were implicated in mitochondrial function and immune activity. Larger studies are needed to confirm our findings and further understand the underlying mechanisms of PFASs exposure in the pathogenesis of SARS-CoV2 infection.